Pengambilan sarapan pagi dan pengaruh ke atas pencapaian kognitif kanak-kanak sekolah rendah - Shazli Ezzat Ghazali; Nor Aini Mohd Yusoff; Ponnusamy S.; Syahiza Abas (penerbit ukm, 2005)
Cognitive development and physical growth among children depend on their nutritional status which include the habit of taking breakfast. The purpose of this study was to determine the effects of breakfast consumption before school on the cognitive performance of primary school children. A cross sectional study was conducted among primary school children in the rural and urban areas. The subjects consisted of 165 Malay students aged 10 years old. Three types of subscales from Wechsler Intelligence Scale For Children-III test were used to measure the cognitive stage of the children, i.e. arithmetic, coding and digit span. The results showed that the performance of students who took breakfast was significantly higher in arithmetic (p<0.05) and digit span(p<0.05) than those who did not take breakfast. This study also found that 62.2% of the subjects from rural areas took breakfast for five consecutive days and 21.7% of subjects from the urban areas did not take breakfast at all. This study showed the importance of taking breakfast among school children to achieve better cognitive abilities.